Vali@mPEG‐TK‐COS: A Dual‐Function Nano‐Pesticide for Fungicidal Action and Plant Immune Modulation - Ruixin Li; Xiaochen Jia; Hongguo Xie; Xueran Wang; Jinxuan Wen; Guanglu Yu; Chunlai Zhang; Yeqing Sun; Heng Yin (Modern Agriculture)
ABSTRACT Pesticides play a crucial role in safeguarding crops against pathogens and pests, yet the limited bioavailability of conventional formulations leads to excessive usage, causing environmental and health concerns. In this study, we developed a novel intelligent response‐controlled release nano‐pesticide, Vali@mPEG‐TK‐COS, by coupling chitosan oligosaccharide (COS), a plant immunity regulator, and methoxy polyethylene glycols (mPEG) at either end of thioketal (TK), a material responsive to reactive oxygen species (ROS), and incorporating validamycin (Vali) for controlled release. Vali@mPEG‐TK‐COS exhibits ROS‐responsive behaviour, releasing Vali and COS in response to plant ROS bursts, exhibiting dual capabilities in pathogen control and plant immunity induction during pathogenic attacks. Plant disease experiments confirmed the superior efficacy of Vali@mPEG‐TK‐COS against Rhizoctonia solani, surpassing the control effects of Vali or COS alone. This study presents a sophisticated ROS‐responsive controlled‐release nano‐pesticide with dual fungicidal and plant immunomodulatory properties, offering an advanced strategy to enhance the efficiency of existing pesticides and promote sustainable crop production by reducing overall pesticide usage.